Game‐theoretic algorithm for interdependent infrastructure network restoration in a decentralized environment - Rangrazjeddi, Alireza; González, Andrés D.; Barker, Kash (Risk analysis, 2024)
Having reliable interdependent infrastructure networks is vital for well‐being of a safe and productive society. Systems are vulnerable to failure or performance loss due to their interdependence among various networks, as each failure can propagate through the whole system. Although the conventional view has concentrated on optimizing the restoration of critical interdependent infrastructure networks using a centralized approach, having a lone actor as a decision‐maker in the system is substantially different from the actual restoration decision environment, wherein infrastructure utilities make their own decisions about how to restore their network service. In a decentralized environment, the definition of whole system optimality does not apply as each decision‐maker's interest may not converge with the others. Subsequently, this results in each decision‐maker developing its own reward functions. Therefore, in this study, we address the concern of having multiple decision‐makers with various payoff functions in interdependent networks by proposing a decentralized game theory algorithm for finding Nash equilibria solutions for network restoration in postdisaster situations.